Surgeons Knowledge, Attitude, and Practice Toward Preoperative Inflammatory Bowel Disease Medications and Post-Operative Complications - Alhassan N; Alnwdel AN; Beyari MB; Aldeligan SH; Alhassan R; Abdulla MH; Bin Traiki T (Therapeutics and Clinical Risk Management)
Noura Alhassan,1 Abdullah Nasser Alnwdel,2 Mohammed Basem Beyari,3 Saleh Husam Aldeligan,3 Reem Alhassan,4 Maha Hamadien Abdulla,1 Thamer Bin Traiki1 1Colorectal Research Chair, Department of Surgery, College of Medicine, King Khalid University Hospital, King Saud University, Riyadh, Saudi Arabia; 2Colorectal Surgery, Department of Surgery, King Fahad Specialist Hospital, Buraydah, Saudi Arabia; 3College of Medicine, King Saud University, Riyadh, Saudi Arabia; 4Pharmacy Department, Prince Sultan Military Medical City, Riyadh, Saudi ArabiaCorrespondence: Mohammed Basem Beyari, Email Mohammedbeyari44@gmail.comBackground: Biologics, particularly anti-TNF agents, have transformed the management of inflammatory bowel disease (IBD), but concerns about their perioperative safety persist.Objective: This study evaluates the knowledge, attitudes, and practices of surgeons in Saudi Arabia regarding the preoperative management of IBD patients undergoing surgery while on biological treatments.Methods: A cross-sectional survey was conducted among 115 surgeons. Participants included general and colorectal surgeons with extensive experience in IBD management. Data were analyzed to assess knowledge, attitudes, and practices related to the impact of biologics, corticosteroids, and immunomodulators on wound healing and postoperative complications.Results: The response rate of 67.8% and Most surgeons (74.4%) believed biologics negatively affect wound healing, despite evidence suggesting their safety. Corticosteroids were unanimously recognized for their adverse effects, while immunomodulators were widely perceived as safe. A majority preferred tapering biologics and corticosteroids 4 weeks preoperatively but continued immunomodulators. Differences between specialties were observed, with colorectal surgeons demonstrating greater adherence to evidence-based guidelines compared to general surgeons, who expressed more concerns about biologics’ risks.Conclusion: This study identifies a persistent gap between evidence and practice in the perioperative management of IBD patients on biologics among Saudi surgeons, with general surgeons often stopping biologics due to safety concerns despite evidence of their safety, while colorectal surgeons are more likely to follow current guidelines. Unnecessary cessation may increase disease flare risk, highlighting the need for targeted education and multidisciplinary collaboration to optimize surgical outcomes.Keywords: inflammatory bowel disease, biologics, corticosteroids, immunomodulators, surgical outcomes